Child-driven, machine-guided: Automatic scaffolding of constructionist-inspired early literacy play. (June 2022) - Sysoev, Ivan; Gray, James H.; Fine, Susan; Makini, Sneha Priscilla; Roy, Deb
Abstract: Child-driven approaches to learning, such as constructionism, can greatly contribute to children's positive relationship with the subject via personally meaningful and grounded learning experiences. However, these approaches typically need scaffolding to ensure learners' progress. Providing scaffolding is nontrivial and time-consuming, typically requiring real-time, one-on-one involvement of the scaffolder. Can scaffolding procedures be at least partially automated? We explored this question in the special case of a constructionist-inspired early literacy app designed for 4- to 6-year-old children. We created scaffolding mechanisms for word building while attempting to preserve the open-ended and child-driven nature of interaction. The system was evaluated during an 11-week-long design study in kindergarten classrooms. We found that scaffolding mechanisms facilitated creative expression and literacy-related social interactions between children, as well as enabled highly autonomous play for some of them. However, despite the scaffolding aid, children with low executive functioning (EF) and phonological awareness (PA) were prone to engage with the app in an impulsive and unsystematic manner, hindering their learning. We discuss possible strategies to mitigate the negative effects of low PA and EF. Despite these challenges, the child-driven, machine-guided approach appears to be promising. Graphical abstract: Image 1 Highlights: Research suggests advantages of both child-driven learning designs and scaffolding. We developed automatic scaffolding for a constructionist-inspired early literacy activity. The scaffolding contributed to players' creative expression, literacy-related social interactions. Players with low phonological awareness and executive function often engaged in chaotic interactions. These interactions appear to have hindered their learning.